Readiness to train: Return to baseline strength and velocity following strength or power training. Issue 2 (April 2020) - Vernon, Alexander; Joyce, Christopher; Banyard, Harry G
This study investigated the return to baseline of movement velocity and maximal strength following a strength-orientated session and power-orientated session in the free-weight back-squat performed with maximal concentric velocity. Fourteen strength-trained males completed a strength-orientated session (five sets of five repetitions @80% of a one-repetition maximum) and a power-orientated session (three sets of six repetitions @50% one-repetition maximum ) in a randomised order over two weeks (e.g. strength week 1, power week 2). The back-squat was then performed with loads of 20%, 40%, 60%, 80%, 90% and 100% one-repetition maximum at 24, 48, 72 and 96 h following the strength and power exercise sessions to assess return to baseline of squat velocity and maximal strength. Dependent variables included one-repetition maximum, back-squat mean velocity and peak velocity and countermovement jump peak velocity. Meaningful changes ((effect size) ≥ −0.60) were reported for mean velocity and peak velocity at loads ≥ 60% one-repetition maximum at 24 and 48 h after the strength-orientated session. Trivial to small (effect size ≤ −0.59) differences were reported for squat velocities following the power-orientated session. Only trivial to small effect size differences were observed for countermovement jump peak velocity and one-repetition maximum at all time points following both sessions. Squat velocity (mean velocity and peak velocity) across the load–velocity profile had recovered at 72 h following the strength-orientated session. However, the return to baseline of squat velocity (mean velocity and peak velocity) did not coincide with the return to baseline of one-repetition maximum or countermovement jump peak velocity. Therefore, measuring and monitoring meaningful changes in velocity may be a more valid and practical alternative in determining full recovery and readiness to train.